2017
DOI: 10.4028/www.scientific.net/jbbbe.30.45
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanocrystal Clay Materials with Potential Bone Cells Growth Enhancement or Inhibition Characteristics <i>In Vitro</i>

Abstract: The application of clay nanocrystals in healing has gained notoriety in recent years. The objective of this work was to investigate whether two medical clay nanocrystals obtained from different geographical locations could exhibit differential cell growth. X-ray diffraction analyses of both nanocrystal materials revealed orthorhombic chamosite structure with lattice parameters: a =15 Å, b= 8 Å and c=7 Å whereas energy dispersive x-ray results showed the presence of Al, Si, Fe and O in both materials. However t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…in the clay minerals are potentially toxic to biological systems. 101 The medical properties of clay minerals have been known by Ghanaians for centuries. They are especially consumed by geophagic people and especially pregnant women.…”
Section: Healthcare Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the clay minerals are potentially toxic to biological systems. 101 The medical properties of clay minerals have been known by Ghanaians for centuries. They are especially consumed by geophagic people and especially pregnant women.…”
Section: Healthcare Applicationsmentioning
confidence: 99%
“…Alternatively, bone growth could be inhibited by clay minerals. 101 Clay materials have high ionic exchange capability. 114 The ionic exchange capability of clays is used in drug delivery to carry appropriate ionic drugs.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The increasing demand for synthetic and natural dyes in the textile, paint and food industries as well as the use of dyes for biomedical research requires efforts to identify new effective adsorbing materials for such applications. Currently activated carbon has gained prominence for water treatment or in removing colored organic substances (Cheng et al, 2018;Khasri & Ahmad, 2018;Tiburu et al, 2017;Yang et al, 2019;Zhou et al, 2019). In addition, Kaolin and montmorillonite clays are abundant in nature with traces of other subtypes spread across continents and have been used as effective color removal agents (Daou et al, 2017;Kenawy et al, 2018;Oussalah et al, 2018;Vanamudan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These clays are widely used for healing purposes due to their perceived efficacy in curing multiple ailments including scorpion bites, chronic headaches, joint and other bodily pains, insanity and female infertility (Van Dongen et al, 2011). Furthermore, recent interest in the analysis of archaeological and ethnographic clays of Ghana (Tiburu et al, 2017;Van Dongen et al, 2011;Insoll, 2011) meant that field archaeologists must go beyond just detailed recording of the matrix as well as past cultural implications to paying greater attention to medicinal and other properties of clay materials from archaeological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research has shown that archeological clay obtained in Komaland, from the Northern Region of Ghana has prospects to enhance human fetal osteoblast cells growth in vitro [25]. Also, other research has shown that treated kaolin from natural clay using chemical and thermal reactions inhibit Hela cervical cancer cells in vitro [26].…”
Section: Introductionmentioning
confidence: 99%